Defects in chondrocyte maturation and secondary ossification in mouse knee joint epiphyses due to Snorc deficiency. Issue 7 (July 2017) - Heinonen, J.; Zhang, F.-P.; Surmann-Schmitt, C.; Honkala, S.; Stock, M.; Poutanen, M.; Säämänen, A.-M.
Summary: Objective: The role of Snorc, a novel cartilage specific transmembrane proteoglycan, was studied during skeletal development using two Snorc knockout mouse models. Hypothesizing that Snorc, like the other transmembrane proteoglycans, may be a coreceptor, we also studied its interaction with growth factors. Methods: Skeletal development was studied in wild type (WT) and Snorc knockout mice during postnatal development by whole mount staining, X-ray imaging, histomorphometry, immunohistochemistry and qRT-PCR. Snorc promoter activity was studied by applying the LacZ reporter expressed by the targeting construct. Slot blot binding and cell proliferation assays were used to study the interaction of Snorc with several growth factors. Results: Snorc expression was localized in the knee epiphyses especially to the prehypertrophic chondrocytes delineating the cartilage canals and secondary ossification center (SOC). Snorc was demonstrated to have a glycosaminoglycan independent affinity to FGF2 and it inhibited FGF2 dependent cell growth of C3H101/2 cells. In Snorc deficient mice, SOCs in knee epiphyses were smaller, and growth plate (GP) maturation was disturbed, but total bone length was not affected. Central proliferative and hypertrophic zones were enlarged with higher extracellular matrix (ECM) volume and rounded chondrocyte morphology at postnatal days P10 and P22. Increased levels of Ihh and Col10a1, and reduced Mmp13 mRNA expression were observed at P10. Conclusions: These findings suggest a role of Snorc in regulation of chondrocyte maturation and postnatal endochondral ossification. The interaction identified between recombinant Snorc core protein and FGF2 suggest functions related to FGF signaling.